Artificial Competence: The Impact of Generative AI Dependency on Students' Critical Thinking and Problem-Solving Agility - Kherismawati, Ni Putu Eka; Suandana, Ni Putu Widantari (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2025)
The integration of Generative AI (GenAI) like ChatGPT into academic environments has promised unprecedented efficiency. However, a growing concern arises regarding "Artificial Competence"—a state where students produce high-quality outputs without possessing the corresponding cognitive mastery. This study investigates the correlation between GenAI dependency and the degradation of critical thinking skills among university students. Utilizing a quantitative approach with 30 respondents, the research measures "Cognitive Offloading" (the tendency to rely on external tools) against "Problem-Solving Agility" (ability to solve complex cases manually). The findings reveal a paradox: while GenAI users report higher confidence levels, their unassisted problem-solving scores are significantly lower than low-frequency users. The study identifies a "Hollow Skill Effect," where dependency on AI creates an illusion of competence, eroding the fundamental cognitive processes required for deep analysis and strategic decision-making.